Hubungan Antara Lingkungan Kerja dan Loyalitas Dengan Motivasi Kerja Karyawan PT. Berkah Pikiran Rakyat Tasikmalaya - Dudu Risana (JURNAL EKONOMI PERJUANGAN, 2019)
This writing is aimed at describing the relationship between work and loyalty environment with the motivation of employees ' work at PT. Blessing of the people of Tasikmalaya, either individually or together.   Writing this poured from research method with the survey method.  Where the research respondents are employees of PT. The people of mind Tasikmalaya as many as 30 employees, from 30 employees were elected based on the census technique. The instrument used is a poll.    The results of this study found that: firstly, there is a positive relationship between the working environment with the motivation of employee work PT. Blessing of People's mind Tasikmalaya.  That means the better the working environment where an employee works, the higher the motivation of the employee's work.  Secondly, there is a positive relationship between loyalty with the motivation of employees work PT. Blessing minds of Tasikmalaya people.Keywords: Work environment, loyalty, work motivation